Modeling and Contact Analysis of Circular-arc-tooth-trace Cylindrical Gear for Manufacture - You Yunxia; Hou Li; Yan Lili; Sun Zhijun (Jixie chuandong)
A modeling method for manufacture of circular-arc-tooth-trace（CATT） cylindrical gear is proposed by analyzing the generating theory and meshing principle of gear and rack.Based on the secondary development of UG software,the three-dimensional model of CATT cylindrical gear for manufacturing is established.The maximum contact stress of CATT cylindrical gear with different tooth line radius are analyzed under the same condition by using the method of finite element analysis.Reveal The influence of the tooth line radius on the contact line length and the maximum contact stress of CATT cylindrical gear and the influence law curve of the maximum contact stress are obtained,which provides the necessary theoretical basis for the design and engineering application of the CATT cylindrical gear.